Perlindungan Hak Warga Negara dalam Negara Demokrasi : Perspektif Konstitusional dan Hak Asasi Manusia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Erlina Hendratama Putri; Najwa Mudya Prameswati; Sri Dewi Indah Dian Purnamasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
In this article, we discuss protection the rights of citizens in democratic countries from a constitutional point of view and human rights (HAM). The constitution, as the highest legal document of a country, contains the basic principles governing the relationship between the state and its citizens, including in terms of human rights protection. By analyzing the framework of Indonesian law, including the Constitution that was adopted in 1945 and various international human rights instruments. The constitution of Indonesia, especially in Article 28A-28J. However, the implementation of these rights still faces various complex challenges, including regulatory inconsistencies, social inequalities, as well as other political, economic and social factors. It is hoped that this article can make a positive contribution to strengthening the human rights protection system in Indonesia, so that the rights of citizens can be guaranteed and protected properly. Normative juridical research method applied in this article includes analysis of legal rules related to human rights protection, including constitutional laws, government regulations, a court decision. With the application of this research method, this article is expected to make a significant contribution to strengthening the human rights protection system in Indonesia, so that the rights of citizens are guaranteed and protected effectively.